Conceptual Framework for Using the Balanced Scorecard as a Source of Increasing the Efficiency of International Freight Transport (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article forms the conceptual basis for using the system of balanced indicators as a source of increasing the efficiency of international freight traffic in the work of domestic trucking enterprises. The methodology is based on the use of the theory of systems, the method of an integrated approach, the theory of activity. The essence of the initial concept of using the system of balanced indicators, which was developed by R. Kaplan and D. Norton, is described, the content of the projections «finance», «clients», «training and career growth (personnel)», «internal business processes» in the context of management a motor transport enterprise engaged in international cargo transportation. Based on the characterization of the content of the projections, it is justified that for domestic trucking enterprises personnel (level of training and development) that provides quality services for arranging international freight traffic (the level of internal business processes) are needed, then the client will be satisfied (the level of prospects for customer development), and the trucking enterprise will achieve strategic financial goals (level of financial prospects). The emphasis is put on the productivity of the staff, its satisfaction. The causal chain of the strategic goals of road transport enterprises has been formed to improve the efficiency of international freight traffic. As a key strategic goal of a trucking enterprise operating in the field of international transportation, the goal is to increase the value of business (or strengthen its position in the market). To ensure the strategic goal, the financial activity of the enterprise should be directed (by increasing its profitability and increasing the productivity of personnel), organization of work with clients (by improving the quality of work with clients, achieving the goals of increasing the number of customers and their loyalty), building internal business- processes (it provides for increasing the efficiency of business processes and the introduction of GPS-monitoring of the operation of transport) and work with personnel (increase in the level of innovation, staffing, increasing the level of staff loyalty to the trucking enterprise). The logic of the development of measures for the introduction of the SSP into the work of road transport enterprises has been determined. The algorithm for implementing the management of a trucking enterprise operating in the field of international freight traffic is presented on the basis of a balanced scorecard, which consists of the following stages: the development of indicators, the identification of a causal relationship, the development of a hierarchy of indicator maps, the establishment of relationships with staff motivation, the preparation of an information technology infrastructure , receiving and recording feedback.
Keywords: international freight transportation, balanced scorecard, efficiency, motor company, strategic goals, algorithm.